Contemporary groups in the genetic evaluation of Nellore cattle using Bayesian inference - Silva, Delvan Alves da; Silva, Fabyano Fonseca e; Ventura, Henrique Torres; Junqueira, Vinícius Silva; Silva, Alessandra Alves da; Mota, Rodrigo Reis; Lopes, Paulo Sávio (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the criteria for the formation of contemporary groups (CGs) in the genetic evaluation of body weight at weaning in Nellore cattle. A total of 713,474 records from 3,066 herds located in Midwestern and Northern Brazil were used. Data were obtained from the genealogical registry of zebu breeds of the Brazilian association of zebu breeders. Data structures were defined based on the number of standard deviations (SDs) for outlier removal (±2.0, ±2.5, ±3.0, and ±3.5) and on the minimal number of animals per CG (3, 7, and 15). Genetic evaluation was performed with an animal model using Bayesian inference. Data structures with ±3.5 SDs and CG with at least 15 animals presented the highest additive genetic variance (82.65±2.93), and those with ±2.0 SDs and CG with at least 3 animals showed the lowest one (60.23±1.96). The proper formation of CGs results in better-quality data archives, allowing to obtain more trustable estimates for the genetic parameters. Better selection responses are obtained when the following criteria are adopted for the removal of outliers: 2.5, 3.0, and 3.5 standard deviations and a minimum of 15 animals per contemporary group.